Disc Geometry is an Accurate Predictor of Lordotic Correction in the Thoracolumbar Spine Following Schwab Grade 2 Osteotomy: A Cadaveric Study and Biomechanical Analysis of Disc Space Changes Following Lordotic Correction. Issue 3 (13th December 2018) - Bohl, Michael A; Hlubek, Randall J; Mooney, Michael A; Chapple, Kristina M; Preul, Mark C; Chang, Steve W; Turner, Jay D; Kakarla, U Kumar
Abstract: BACKGROUND: Posterior column osteotomy (PCO) is a powerful technique for correcting lordosis, but the surgical literature lacks objective evidence on preoperative predictors of achievable lordotic correction following PCO. OBJECTIVE: To measure the correlation between disc geometry and achievable lordotic correction following Schwab grade 2 osteotomies and to describe geometric changes to disc space following lordotic correction. METHODS: Schwab grade 2 osteotomies were performed from T1 to S1 in 5 cadavers. Lateral radiographs were taken before and after posterior column compression. Anterior disc height (ADH), middle disc height (MDH), posterior disc height (PDH), and lordotic angles were measured. The association between disc height and lordotic correction was analyzed using linear regression. RESULTS: For all spinal levels (n = 79), PDH was most strongly correlated with lordotic correction ( r  = 0.72, P  < .001). Regional subset analyses showed the strongest correlation between PDH and lordotic correction achievable within the lumbar spine (n = 22, r  = 0.77, P  < .001), followed by ADH for lower thoracic spine (n = 29, r  = 0.65, P  < .001) and PDH for upper thoracic spine (n = 28, r  = 0.61, P  = .001). Postcorrection analysis of disc heights revealed that as lordotic correction increases, the PDH decreases, and the ADH expands. CONCLUSION: PDH is a strong predictor of achievable lordotic correction following Schwab grade 2 osteotomies and compression of an intact disc space. In the lumbar spine, 50% of lordotic change is predictable using PDH alone. Further testing of our linear regression equation is planned for prospective clinical studies, and further testing of postcorrection disc space geometry is planned for future biomechanical and surgical technique studies.